Factors Affecting Customer Satisfaction Of The Ubud Anyer Hotel - Zenia Dinka Irawan; Herry Goenawan Soedarsa (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to find out the influence of the quality of your service and civil service on customer satisfaction at the Ubud Anyer Hotel. As well as identifying the factors that influence customer satisfaction. Population study This is customers staying at the Ubud Hotel Anyer with criteria aged 17-25 years, with amount sample of 30 people. This research uses test tools in the form of validity tests and reliability tests.The data analysis technique used in this research is analysis multiple linear regression. As well as Test hypothesis using the F test and T test. From the results of the researcher and the discussion, conclusions can be drawn about the quality of service and the existing facilities owned by Hotel Ubud Anyer has an influence on customer satisfaction.